The Role of Claim-Makers in Media Coverage of Environmental Problems in Pakistan - Hingorjo, Ali Akbar; Memon, Bashir (Progressive Research Journal of Arts & Humanities (PRJAH), 2020)
Media coverage plays an important role in social construction of environmental issues all over the world. The coverage is often triggered by the claim-makers who play an active role in highlighting the environmental issues in media. In this context, this study is aimed at analyzing the role of claim-makers in media coverage of the environmental problems in Pakistan. The region of Indus Delta is selected as a case study for this research because this deltaic area is considered as one of the most highly productive eco-region of the country that is facing several environmental threats. The study provides the perspective of journalists covering the Indus Delta about the role of non-governmental organizations, political parties, community groups and concerned governmental bodies and departments in making the environmental problems of the region more news worthy for local and national media. Then the main themes of the data were analyzed and interpreted to answer the research questions of the study.